PERANAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE BERBANTUAN MEDIA AUDIO VISUAL PADA PEMBELAJARAN IPS ERA MILENIAL - Fatmawati, Yuyun; Rizal, Abda Rifki (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
To fulfill education in the current millenial generation, educators always make interesting innovations that can make students’ interests increase. The development of teaching concepts by applying learning principles, models and interactive media to social studies learning continues. The application of social values in the Value Clarification Technique (VCT) learning model through the help of audio visual media into social studies lessons, students can instiil social values individually as well as learning experiences for real life provision. In addition, students not only have cognitive aspects, but also have adventages in the affective aspects which are certainly needed in the millenial era.